Mineral content variability of two dry-cured ham types - Kos, Ivica (Array, 2021)
The aim of this study was to elaborate on the mineral content variability of two dry-cured ham types for better understanding of the contribution of minerals to reference daily intake (RDI). These two ham types were based on Istrian and Dalmatian ham manufacturing process. Significantly higher (P<0.05) contents of ash, NaCl, sodium (Na), potassium (K), phosphorus (P), zinc (Zn), iron (Fe), copper (Cu), and manganese (Mn) were found in Istrian ham, while Dalmatian ham had higher moisture content. Calcium (Ca) and magnesium (Mg) content did not differ between ham types. The variability of moisture, ash, NaCl, Na, P, Mg, and Ca content can be regarded as low, while the variability of K, Zn, Fe, Cu, and Mn content should be considered as high. It was observed that mineral content variability within ham type was more often lower than overall variability. Intake of Na by consumption of 100 g of dry-cured ham is between 2350.54 mg in Dalmatian ham and 3148.33 mg in Istrian ham, respectively, thus exceeding recommended daily limitation. Therefore, more efforts in ham manufacturing have to be done to lower Na content. Average contribution of K, P, and Zn to the RDI values were 31.89 %, 40.14 %, and 50.80 %, respectively. Considering that, dry-cured ham could be regarded as a source of a significant amount of these minerals. Contribution of Fe and Cu should be carefully considered because of high variability between ham types. Contribution of Mg, Ca, and Mn to RDI values were lower than 10 %.